Analisis Hubungan Tingkat Pendapatan dan Pengetahuan dengan Perilaku Ibu Terhadap Gizi Balita Di Wilayah Kerja Puskesmas Sungai Besar Kota Banjarbaru Tahun 2017 - Ari Widyarni (HB PRESS, 2017)
Prevalence of malnutrition in Kalimantan Selatan in 2013 reached 103 people, 8 people (7,8%) of whom died. Increased in 2015 malnutrition sufferers there are 143 Balita and 15 Balita (10,5%) of whom died due to the infection is quite severe. The average of toddler suffering from malnutrition that passed away from poor families.This research is a quantitative study with cross sectional approach. Population and sample are mother Balita in work area of Sungai Besar Public Health Center which amounted to 96 people. The data taken in this study is primary data through in-depth interviews using structured questionnaires by taking accidental sampling. Bivariate analysis using Spearman Rank correlation test.The result of the research on 96 respondents found the income level of Balita families which is calculated based on the per capita in general less than the average were 71,8%, the knowledge of the mother about toddler nutrition was mostly enough that is 60,4% and the mother's behavior toward the nutrition of toddler was enough at 50.0%. There was a significant relation between income level with mother behavior (r = 0,392, p = 0,000) and between knowledge level with behavior of mother (r = 0,740, p = 0,000) on nutrition toddler in work area of Sungai Besar Public Health Center. It is hoped Dinas Kesehatan Banjarbaru City can add work programs related to the prevention of malnutrition problems such as posting posters in public places, increase counseling about nutrition of Toddler, distribute pamphlets of nutrition to mothers who bring toddler to Public Health Center